Answer:
Explanation:
Given:
x = t^2 - 4t
y = √t + 1
Making t the subject of formula from equation 2,
t = (y - 1)^2
Inputting into equation 2,
x = (y - 1)^4 - 4 × (y - 1)^2
= (y - 1)^2 ((y - 1)^2 - 4)
= (y^2 - 2y + 1) × (y^2 - 2y + 1 - 4)
= (y^2 - 2y + 1) × (y^2 - 2y - 3)
= y^4 - 2y^3 - 3y^2 - 2y^3 + 4y^2 + 6y + y^2 - 2y - 3
x = y^4 - 4y^3 + 2y^2 + 4y - 3
x = (y - 1) × (y - 1) × (y - 3) × (y + 1)
The above equation of x and y is a function because the dependent variable, x is dependant on the values of the independent variable, y.